1984
DOI: 10.1093/jn/114.7.1327
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism, Plasma Transport and Biliary Excretion of Radioactive Vitamin A and its Metabolites as a Function of Liver Reserves of Vitamin A in the Rat

Abstract: Groups of 7-12 weanling Sprague-Dawley male rats were fed graded daily doses of vitamin A (5-176 micrograms retinol) for 7 or 12 weeks. Final mean liver concentrations of vitamin A, which ranged from 0.4 to 331 micrograms retinol per gram, depended both on the daily dose given and on the length of the feeding period. The mean serum retinol concentration was 24 micrograms/dl at the lowest liver vitamin A concentration, approached a plateau of 40 micrograms/dl at a liver concentration of 5-10 micrograms/g, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 17 publications
2
50
1
Order By: Relevance
“…To account for the fact that unlabelled retinol is continuously consumed in the diet and newly absorbed retinol contributes preferentially to the plasma pool, another factor is applied to correct for the difference in specific activity in liver compared with plasma. A value of 0.65 is usually assumed, derived from the ratio observed in rats (Hicks et al, 1984). This factor is not needed if no retinol, or as little as possible, is consumed during the equilibration period.…”
Section: Indirect Measurement By Stable Isotope Dilution Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To account for the fact that unlabelled retinol is continuously consumed in the diet and newly absorbed retinol contributes preferentially to the plasma pool, another factor is applied to correct for the difference in specific activity in liver compared with plasma. A value of 0.65 is usually assumed, derived from the ratio observed in rats (Hicks et al, 1984). This factor is not needed if no retinol, or as little as possible, is consumed during the equilibration period.…”
Section: Indirect Measurement By Stable Isotope Dilution Methodsmentioning
confidence: 99%
“…as free retinol and retinyl esters) as a criterion to define adequate vitamin A status, based on the following considerations: (1) no clinical signs of deficiency have been noted in individuals with this or a higher liver concentration; (2) at this concentration and above, the liver is capable of maintaining a steadystate plasma retinol concentration, as determined by the relative dose-response test in rats (Loerch et al, 1979) and humans (Amedee-Manesme et al, 1987); (3) biliary excretion of retinol increases significantly when liver stores rise significantly above this concentration in rats (Hicks et al, 1984), which is suggested to serve as a regulatory mechanism of vitamin A storage; and (4) this concentration was calculated to be sufficient to protect an adult ingesting a diet free of vitamin A from a deficiency state for approximately four months as well as to meet vitamin A needs during shorter periods of stress (e.g. infection).…”
Section: Total Body Retinol Content and Liver Retinol Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Thus, to be more broadly applicable, the correction for 12 F is a factor to express efficiency of storage (estimated to be 0. 5 49 ); S is the ratio of specific activity of retinol in plasma to specific activity of VA in liver (taken as 0.65 from a rat study 50 ); a is the fraction of absorbed tracer dose remaining in body at time t after dosing (a ¼ e Àkt , using an estimated rate of catabolism of VA for adults; k ¼ [ln 2]/140 days ¼ 0.00495 per day); H:D is the isotope ratio of nondeuterated (tracee) to deuterated (tracer) retinol in plasma; and the term ''À1'' is used to correct for the contribution of the mass of the tracer dose to the total VA stores (not needed when the tracer dose is small)…”
Section: Evolution Of Stable Isotope Dilution Techniques For Determinmentioning
confidence: 99%
“…Furr et al included the factor S (the ratio of vitamin A specifi c activity in plasma vs. liver), estimated as 0.65, to account for the dilution of the tracer/tracee ratio as unlabeled vitamin A (tracee) enters the system from the diet, and tracer and tracee are lost by catabolism. The value for S was based on earlier studies in Olson's lab on the metabolism of vitamin A in rats as a function of liver vitamin A stores [11]. Also related to catabolism, and thus loss of tracer, the factor a was introduced as a correction.…”
Section: "Olson Equation" and Underlying Assumptionsmentioning
confidence: 99%